2008
DOI: 10.1016/j.jneumeth.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic constriction injury of the infraorbital nerve in the rat using modified syringe needle

Abstract: Here we report a method for performing a chronic constriction injury (CCI) of the infraorbital nerve (ION) in the rat as a component of a chronic pain model. The surgical approach to the ION is described together with the use of a modified dental syringe needle that simplifies placing two chromic gut ligatures around the ION. This method makes the surgical procedure easier, the nerve injury more consistent across animals and reduces secondary damage to the ION and surrounding tissue. Pain behavior testing toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 19 publications
0
54
1
Order By: Relevance
“…3B. Importantly, it is also of note that our results show a role of NMDA, but not AMPA, receptors in the DRG in the development of inflammatory hyperalgesia, whereas those authors have shown the involvement of other types of GLU receptors in a model of neuropathic pain [i.e., chronic constriction injury (40,41)]. These findings suggest the involvement of different types of GLU receptors in the DRG during inflammatory and neuropathic hyperalgesia.…”
Section: Resultscontrasting
confidence: 38%
“…3B. Importantly, it is also of note that our results show a role of NMDA, but not AMPA, receptors in the DRG in the development of inflammatory hyperalgesia, whereas those authors have shown the involvement of other types of GLU receptors in a model of neuropathic pain [i.e., chronic constriction injury (40,41)]. These findings suggest the involvement of different types of GLU receptors in the DRG during inflammatory and neuropathic hyperalgesia.…”
Section: Resultscontrasting
confidence: 38%
“…IoN-CCI 25 , the application of complete Freund’s adjuvant (CFA) to the orbital portion of the IoN 3 , and unilateral partial ligation of the IoN (pIONL) 1, 28 are three commonly used animal models to study trigeminal neuropathic pain. All IoN-CCI procedures described and used by others are also complex and difficult to perform 10, 12, 13, 25 . In this report, we showed an improved model of IoN-CCI by 1) using a 0.5 cm facial incision to access the IoN trunk outside the orbital cavity and 2) placing two ligatures at the distal IoN just before the IoN branches into the whisker pad.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature indicates that chronic constriction injury of the IoN has been performed by placing two chromic gut ligatures on the IoN trunk either inside 13, 25 or outside 10, 12 the orbital cavity. Both midline 25 and eye lid 13 incisions have been used to gain access to the IoN segment inside the orbital cavity, and in either case the orbital contents are affected. The placement of ligatures on the intraorbital segment of the IoN presses the orbital contents and may cause eye discomfort, leading to increased grooming activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, various kinds of experimental animal models have been employed to clarify the mechanisms of neuropathic pain, including allodynia, in the trigeminal region. These models involved rats or large animals and were limited to the infraorbital nerve (Benoist et al, 1999;Bird et al, 2002;Elcock et al, 2001;Grelik et al, 2005;Henry et al, 2007;Imamura et al, 1997;Kernisant et al, 2008;Kitagawa et al, 2006;Lim et al, 2007;Long et al, 1998;Vos et al, 1994Vos et al, , 1995. The development of an experimental model involving mice will enable us to provide new insights into the mechanisms of sensory disorders owing to the possibility of using various gene targeting procedures.…”
Section: Introductionmentioning
confidence: 99%